Pembentukan Karakter Religius Peserta Didik Melalui Pembiasaan Kegiatan Keagamaan di Madrasah Ibtidaiyah Bantarsari - Nur Laeli (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2023)
This research aims to describe the formation of students' religious character and students' religious activities at MI Al Muttaqin Bantarsari. This research uses a qualitative approach with analytical descriptive methods. The research subjects were madrasa heads, teachers, employees and students. Data collection techniques in this research used interviews, observation and documentation. Data analysis uses the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results of this research show that the formation of the religious character of students at MI Al Muttaqin Bantarsari is carried out through habituation to religious activities, which starts from learning in the classroom by providing material that refers to the curriculum, syllabus and RPP, then implemented through habituation to religious activities. These religious activities are Cultivating 5S (Greetings, Smiles, Greetings, Politeness, Manners); Dress neatly, cleanly and cover your private parts; Habit of Duha and Midday Prayers in Congregation; Reading Nadzam Asmaul Husna and praying at the beginning and end of learning; Maintaining Cleanliness and Complying with Madrasah Rules and Regulations; Friday Koran; Habituation of Infaq/Jariyah; and the Kilat Ramadhan Islamic Boarding School. The implementation of religious activities is carried out based on a predetermined time. Evaluation of activities is carried out in various ways, there are weekly, monthly and annual evaluations. This evaluation was carried out to determine the extent of the positive impact and influence of religious activities on students and their suitability with the madrasah's vision and mission.